Unveiling the impacts of metformin on hepatocellular carcinoma: A bioinformatic exploration in cell lines - Soraya, Soraya; Arfianti, Arfianti; Adikusuma, Wirawan; Irham, Lalu M.; Hamidy, Muhammad Y.; Winarto, Winarto; Rangkuti, Ina F.; Darmawi, Darmawi (Narra Sains Indonesia, 2024)
The most common type of liver cancer is hepatocellular carcinoma (HCC), accounting for 75–85% of cases. Despite its associated side effects, sorafenib remains the standard treatment for HCC. Given the critical need to improve therapeutic efficacy while minimizing adverse effects, alternative drugs must be thoroughly investigated. Numerous studies indicate that combining sorafenib with metformin results in a more favorable treatment profile. The aim of this study was to employ bioinformatics methodologies to elucidate the molecular pathways and genetic underpinnings of metformin's efficacy in HCC treatment. Genes associated with metformin and its action against HCC (Huh-7 and HepG2 cells) were acquired from the NCBI-GEO data collection by utilizing pre-determined keywords. Subsequently, pathways implicated in metformin-mediated HCC treatment were analyzed through the Kyoto Encyclopedia of Genes and Genomes (KEGG). Our analysis revealed the involvement of multiple pathways, with metabolic pathways implicated in 80% of the total cases. Neurodegenerative pathways were involved in only around 60% of the total cases. These findings align with the multifaceted mechanisms of metformin’s action, encompassing adenosine monophosphate-activated protein kinase activation, apoptosis induction, insulin regulation, anti-inflammatory responses, and modulation of cell proliferation. This comprehensive investigation sheds light on the intricate molecular landscape underpinning metformin's therapeutic efficacy in HCC, thereby informing potential avenues for optimizing treatment strategies.